Biallelic mutation in MYH7 and MYBPC3 leads to severe cardiomyopathy with left ventricular noncompaction phenotype. Issue 8 (24th April 2019) - Kolokotronis, Konstantinos; Kühnisch, Jirko; Klopocki, Eva; Dartsch, Josephine; Rost, Simone; Huculak, Cathleen; Mearini, Giulia; Störk, Stefan; Carrier, Lucie; Klaassen, Sabine; Gerull, Brenda
Abstract: Dominant mutations in the MYH7 and MYBPC3 genes are common causes of inherited cardiomyopathies, which often demonstrate variable phenotypic expression and incomplete penetrance across family members. Biallelic inheritance is rare but allows gaining insights into the genetic mode of action of single variants. Here, we present three cases carrying a loss‐of‐function (LoF) variant in a compound heterozygous state with a missense variant in either MYH7 or MYBPC3 leading to severe cardiomyopathy with left ventricular noncompaction. Most likely, MYH7 haploinsufficiency due to one LoF allele results in a clinical phenotype only in compound heterozygous form with a missense variant. In contrast, haploinsufficiency in MYBPC3 results in a severe early‐onset ventricular noncompaction phenotype requiring heart transplantation when combined with a de novo missense variant on the second allele. In addition, the missense variant may lead to an unstable protein, as overall only 20% of the MYBPC3 protein remain detectable in affected cardiac tissue compared to control tissue. In conclusion, in patients with early disease onset and atypical clinical course, biallelic inheritance or more complex variants including copy number variations and de novo mutations should be considered. In addition, the pathogenic consequence of variants may differ in heterozygous versus compound heterozygous state.